The power of online reviews: Exploring information asymmetry and its impact on green product purchasing behavior - Ikhsan, Ridho Bramulya; Fernando, Yudi; Gui, Anderes; Fernando, Erick (John Wiley and Sons Inc., 2024)
Manufacturers must convey accurate information about their green products to gain consumer trust. However, some manufacturers provide misleading information by falsely claiming that their products fully adhere to green concepts. Consequently, research is needed to examine customer behaviors and how they respond to information about green products. This study models the relationship between green product information asymmetry, online review quality, the propensity to trust and adopt reviews, and green product purchasing behavior. The study participants were 479 consumers who purchased green products. Data for the study were collected through an online questionnaire that was distributed on social media platforms and analyzed using partial least squares structural equation modeling. The results show that information asymmetry positively affected online review quality, review adoption, and green product purchasing behavior, while online review quality positively affected participants' propensity to trust reviews, review adoption, and purchasing behavior. The propensity to trust reviews positively affected review adoption and purchasing behavior, and review adoption positively impacted green product purchases. These results show that information asymmetry highlights the importance of consumer reviews in green product purchasing behavior. Therefore, both information asymmetry and consumer reviews influence green-product consumption. When constructing green marketing strategies, green product manufacturers must focus on a combination of perceived value and consumer trust and modify their products, production processes, packaging, and advertisements accordingly.